Interior materials and methods for manufacturing the same

JP7936858B2Active Publication Date: 2026-10-16TOLI
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2024207900
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2026-10-16
Estimated Expiration
2042-03-30

Smart Images

  • Figure 0007936858000002
    Figure 0007936858000002
  • Figure 0007936858000003
    Figure 0007936858000003
  • Figure 0007936858000004
    Figure 0007936858000004
Patent Text Reader

Abstract

To provide an interior material having both low luster and antifouling properties.SOLUTION: An interior material 1 includes a base material 2 and an active energy ray curable resin layer 3 comprising a cured body of an active energy ray curable resin composition 30 laminated on the base material 2, wherein a surface 3a of the active energy ray curable resin layer 3 has an uneven structure 4 satisfying the following surface roughness parameters (1)-(3): (1) an arithmetic mean height (Sa) is 0.5 to 6 μm; (2) an average arithmetic curvature (Spc) of a tip of a convex part 4a is 300 to 1,300 μm-1; and (3) when a projected area of the uneven structure 4 is S1 when projected onto a flat surface, and when a difference between an actual surface area of the uneven structure 4 and the projected area S1 is S2, a development area ratio (Sdr) expressed as S2 / S1 is 0.05 to 0.2.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to an interior material comprising a base material and an active energy ray curable resin layer laminated on the base material, and a method for manufacturing the same. [Background technology]

[0002] Interior materials such as flooring and wall coverings are made of materials with a low-gloss surface.

[0003] As an example of this type of interior material, a decorative sheet (interior material) has been proposed in which a UV-curable resin layer containing powder such as silica is laminated onto a base material, and a fine uneven surface structure is formed by the powder (see, for example, Patent Document 1).

[0004] Furthermore, decorative sheets (interior materials) and building materials (interior materials) have been proposed in which a coating solution containing an ultraviolet-curable resin is applied to a substrate, the surface of the coating solution is partially cured by irradiating it with excimer laser light, and then the entire coating solution is cured by irradiating it with ultraviolet light, thereby forming an ultraviolet-curable resin with a fine uneven surface (see, for example, Patent Documents 2 and 3). [Prior art documents] [Patent Documents]

[0005] [Patent Document 1] Japanese Patent Publication No. 2021-165033 [Patent Document 2] Japanese Patent Publication No. 2021-24102 [Patent Document 3] Japanese Patent Publication No. 2018-164901 [Overview of the project] [Problems that the invention aims to solve]

[0006] In interior materials, there is a demand for materials that excel in both low gloss and stain resistance. In this regard, while the interior materials described in Patent Documents 1 to 3 can achieve low gloss through their formed uneven structure, their stain resistance (hereinafter also simply referred to as "stain resistance") as expressed by the heel mark test is insufficient. This is because there is a trade-off relationship between low gloss and stain resistance.

[0007] This invention has been made in view of the above-mentioned problems, and aims to provide an interior material that achieves both low gloss and stain resistance, and a method for manufacturing the same. [Means for solving the problem]

[0008] The characteristic configuration of the interior material according to the present invention, which solves the above problems, is An interior material comprising a base material and an active energy ray curable resin layer laminated on the base material, the active energy ray curable resin layer being made of a cured body of an active energy ray curable resin composition, The surface of the active energy ray curable resin layer has an uneven structure that satisfies the following surface roughness parameters (1) to (3). (1) The arithmetic mean height (Sa) is 0.5 to 6 μm. (2) The mean arithmetic curvature (Spc) of the tip of the convex part is 300 to 1300 μm -1 That is the case. (3) When the projection area of ​​the uneven structure is projected onto a flat surface is S1, and the difference between the actual surface area of ​​the uneven structure and the projection area S1 is S2, the developed area ratio (Sdr) expressed as S2 / S1 is 0.05 to 0.2.

[0009] The interior material of this configuration comprises a base material and an active energy ray curable resin layer laminated on the base material, which is made of a cured body of an active energy ray curable resin composition. The surface of the active energy ray curable resin layer has an uneven structure that satisfies the surface roughness parameters (1) to (3) above. The uneven structure of the surface of the active energy ray curable resin layer is suitable for exhibiting both low gloss and stain resistance, as indicated by the degree of protrusion of the convex parts (protrusion length) indicated by the arithmetic mean height (Sa), the degree of sharpness of the tips of the convex parts (sharpness of the tips of the convex parts) indicated by the mean arithmetic curvature (Spc) of the tips of the convex parts, and the degree of inclination of the uneven structure, indicated by the developed area ratio (Sdr) expressed as S2 / S1, where S1 is the projected area when the uneven structure is projected onto a flat surface, and S2 is the difference between the actual surface area of ​​the uneven structure and the projected area S1. The performance characteristics achieved by specifying the three surface roughness parameters described above, combined, result in an active energy ray curable resin layer having a fine uneven structure that satisfies these surface parameters, making it suitable for exhibiting both low gloss and stain resistance. As a result, the interior material achieves a balance between low gloss and stain resistance.

[0010] In the interior material according to the present invention, The aforementioned uneven structure is preferably further satisfied with the surface roughness parameter (4) below. (4) The maximum height (Sz) is 5 to 50 μm.

[0011] With this interior material configuration, the uneven structure further satisfies the surface roughness parameter (4) above, so that the degree of local protrusion (protrusion length) of the protrusions, indicated by the maximum height (Sz), becomes suitable for exhibiting both low gloss and stain resistance. As a result, the performance exhibited by specifying the maximum height (Sz) in addition to the three surface roughness parameters above combines to make the surface of the active energy ray cured resin layer having the above-mentioned uneven structure more suitable for exhibiting both low gloss and stain resistance. Thus, the interior material achieves a high level of both low gloss and stain resistance.

[0012] In the interior material according to the present invention, The active energy ray-curable resin composition preferably contains a polyfunctional urethane acrylate and a polyfunctional acrylate monomer.

[0013] According to the interior material of the present configuration, since the active energy ray-curable resin composition contains the polyfunctional urethane acrylate and the polyfunctional acrylate monomer, a practical interior material having both appropriate elasticity derived from the polyfunctional urethane acrylate and appropriate rigidity derived from the polyfunctional acrylate monomer can be obtained.

[0014] In the interior material according to the present invention, The mass ratio (a:b) of the mass (a) of the polyfunctional urethane acrylate to the mass (b) of the polyfunctional acrylate monomer is preferably 10 to 90:90 to 10.

[0015] According to the interior material of the present configuration, by setting the mass ratio (a:b) of the polyfunctional urethane acrylate (a) to the polyfunctional acrylate monomer (b) to 10 to 90:90 to 10, a more excellent interior material with balanced elasticity and rigidity can be obtained.

[0016] The characteristic configuration of the method for producing an interior material according to the present invention for solving the above problems is as follows: The method for producing the interior material comprises: an application step of applying the active energy ray-curable resin composition to the base material; a first irradiation step of irradiating the active energy ray-curable resin composition with excimer laser light; a second irradiation step of irradiating with ultraviolet rays or electron beams after the first irradiation step; The method includes the above steps.

[0017] According to the method for producing an interior material of the present configuration, by including the application step, the first irradiation step, and the second irradiation step, it is possible to form an active energy ray-curable resin layer having a fine uneven structure whose surface roughness parameters satisfy the above (1) to (3) on a base material. As a result, as described above, the performances exhibited by the specification of the three surface roughness parameters combine to make the surface of the active energy ray-curable resin layer suitable for exhibiting both low glossiness and antifouling properties. Therefore, according to the method for producing an interior material, it is possible to produce an interior material that achieves both low glossiness and antifouling properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] [Figure 1] Figure 1 is a cross-sectional view schematically showing the laminated structure of an interior material according to an embodiment of the present invention, together with its production method and an enlarged view of the surface uneven structure. [Figure 2] Figure 2 is a diagram showing the interior material according to Example 1, where Figure 2(a) is a laser micrograph of the surface, and Figure 2(b) is a three-dimensional image of the region photographed with a laser microscope. [Figure 3] Figure 3 is a diagram showing the interior material according to Example 2, where Figure 3(a) is a laser micrograph of the surface, and Figure 3(b) is a three-dimensional image of the region photographed with a laser microscope. [Figure 4] Figure 4 is a diagram showing the interior material according to Example 3, where Figure 4(a) is a laser micrograph of the surface, and Figure 4(b) is a three-dimensional image of the region photographed with a laser microscope. [Figure 5] Figure 5 is a diagram showing the interior material according to Comparative Example 1, where Figure 5(a) is a laser micrograph of the surface, and Figure 5(b) is a three-dimensional image of the region photographed with a laser microscope. [Figure 6] Figure 6 is a diagram showing the interior material according to Comparative Example 2, where Figure 6(a) is a laser micrograph of the surface, and Figure 6(b) is a three-dimensional image of the region photographed with a laser microscope. [Figure 7]Figure 7 shows the interior material relating to Comparative Example 3, where Figure 7(a) is a laser microscope image of the surface and Figure 7(b) is a three-dimensional image of the region captured by the laser microscope. [Modes for carrying out the invention]

[0019] Hereinafter, an embodiment of the interior material of the present invention will be described with reference to the drawings. In each drawing, the thickness relationships and uneven structures of each layer have been exaggerated or simplified as appropriate for the sake of clarity, and do not strictly reflect the relative thicknesses (scale) and uneven structures of each layer in actual interior materials.

[0020] In this specification, the "surface" of the active energy ray-curable resin layer formed on the substrate refers to the side opposite to the substrate, i.e., the side exposed to the outside. Furthermore, "active energy ray-curable resin (composition)" means an uncured resin or resin composition that has the property of curing by irradiation with active energy rays, and "active energy ray-curable resin" means a resin in the state in which the active energy ray-curable resin (composition) has been cured by irradiation with active energy rays. The active energy rays used in the embodiments of the present invention are excimer laser light and ultraviolet light.

[0021] <Overall composition of interior materials> Figure 1 is a schematic cross-sectional view showing the laminated structure of an interior material 1 according to one embodiment of the present invention, along with its manufacturing method and surface uneven structure. The interior material 1 shown in Figure 1 is an interior material comprising a base material 2 and an active energy ray curable resin layer 3 laminated on the base material 2, which is made of a cured body of an active energy ray curable resin composition 30.

[0022] <Base material> The base material 2 constitutes the main body of the interior material 1, and an active energy ray curable resin layer 3 is laminated on its surface 2a. The material of the base material 2 is not particularly limited and can be, for example, resins such as flexible polyvinyl chloride or rigid polyvinyl chloride, or inorganic materials such as ceramics. The interior material 1 can be used as a conventionally known flooring material, wall material, etc. In particular, polyvinyl chloride resin is suitable as a flooring material because of its excellent processability and strength.

[0023] The thickness of the base material 2 is preferably 1 mm or more, and more preferably 5 mm or more. A thickness of 1 mm or more for the base material 2 enhances the strength of the interior material 1. There is no particular upper limit to the thickness of the base material 2, but it can be, for example, 100 mm or less.

[0024] <Activated energy ray curing resin layer> As shown in Figure 1, the active energy ray curable resin layer 3 consists of a cured body of an active energy ray curable resin composition 30 laminated on the substrate 2, and the surface 3a of the active energy ray curable resin layer 3 is configured to have an uneven structure 4. This uneven structure 4 forms wrinkles, as shown in Figures 2 to 4 which will be described later.

[0025] The surface 3a of the active energy ray curable resin layer 3 has an uneven structure 4 that satisfies the following surface roughness parameters (1) to (3). (1) The arithmetic mean height (Sa) is 0.5 to 6 μm. (2) The mean arithmetic curvature (Spc) of the tip of the convex portion 4a is 300 to 1300 μm -1 That is the case. (3) When the uneven surface structure 4 is projected onto a flat surface, let S1 be the projected area, and let S2 be the difference between the actual surface area of ​​the uneven surface structure 4 and the projected area S1, the developed area ratio (Sdr) expressed as S2 / S1 is 0.05 to 0.2. The inventors, through diligent research into various parameters that serve as indicators of uneven structures and the numerous possible combinations thereof, discovered that the performance exhibited by specifying the above-mentioned surface roughness parameters (1) to (3) combined results in a surface of an active energy ray curable resin layer having a fine uneven structure that satisfies these surface parameters being suitable for exhibiting both low gloss and stain resistance.

[0026] The arithmetic mean height (Sa) is an indicator of the overall degree of protrusion (protrusion length) of the convex parts 4a of the uneven structure 4. The smaller the arithmetic mean height (Sa), the smaller the overall protrusion length of the convex parts 4a, and consequently, the smaller the overall depth of the concave parts 4b. On the other hand, the larger the arithmetic mean height (Sa), the larger the overall protrusion length of the convex parts 4a, and consequently, the larger the overall depth of the concave parts 4b. An arithmetic mean height (Sa) of 0.5 to 6 μm results in an overall protrusion length of the convex parts 4a that is suitable for low gloss and stain resistance. The arithmetic mean height (Sa) is calculated as the average value measured at any ten points on the surface 3a of the active energy ray curable resin layer 3.

[0027] The arithmetic mean height (Sa) is preferably 2 to 5 μm. When the arithmetic mean height (Sa) is 2 to 5 μm, the uneven structure 4 of the surface 3a of the active energy ray curable resin layer 3 is more suitable for exhibiting both low gloss and stain resistance, as indicated by the degree of protrusion (protrusion length) of the convex portions 4a. As a result, the interior material 1 achieves a high level of both low gloss and stain resistance.

[0028] The mean arithmetic curvature (Spc) of the tip (apex) of the convex part 4a is an indicator of the degree of sharpness of the tip of the convex part 4a. The mean arithmetic curvature (Spc) represents the curvature at the vertex when the convex part 4a is numerically represented quadratically as a parabola. A smaller mean arithmetic curvature (Spc) indicates a more rounded tip of the convex part 4a. Conversely, a larger mean arithmetic curvature (Spc) indicates a sharper tip. Mean arithmetic curvature (Spc) of 300-1300 μm -1As a result, the sharpness of the protrusion 4a is suitable for low gloss and stain resistance. The average arithmetic curvature (Spc) of the tip of the protrusion 4a is calculated as the average value measured at any ten points on the surface 3a of the active energy ray curable resin layer 3.

[0029] The mean arithmetic curvature (Spc) is 400-1200 μm. -1 Preferably, the mean arithmetic curvature (Spc) is 400 to 1200 μm. -1 As a result, the uneven structure 4 of the surface 3a of the active energy ray curable resin layer 3 is better suited to exhibiting both low gloss and stain resistance, as the degree of sharpness of the tips of the convex portions 4a, as indicated by the mean arithmetic curvature (Spc), is optimized. This allows the interior material 1 to achieve a high level of both low gloss and stain resistance.

[0030] When the uneven surface structure 4 is projected onto a flat surface, its projected area is S1. When the difference between the actual surface area of ​​the uneven surface structure 4 and the projected area S1 is S2, the developed area ratio (Sdr), expressed as S2 / S1, is an indicator of the degree of inclination of the convex parts 4a and concave parts 4b of the uneven surface structure 4. The developed area ratio (Sdr) is expressed as the ratio S2 / S1 of the projected area S1 when the uneven surface structure 4 is projected onto a flat surface and the difference (increase) S2 between the actual surface area of ​​the uneven surface structure 4 and the projected area S1. It is expressed as a numerical value in the range of 0 to 1 (dimensionless). When the developed area ratio (Sdr) is smallest (Sdr=0), the above difference S2 is 0, and the actual surface area matches the projected area S1. Therefore, the uneven surface structure 4 is not formed on the surface 3a, and there is no inclination at all. As the unfolded area ratio (Sdr) increases, the difference S2 increases, meaning that the actual surface area is larger than the projected area S1, resulting in a greater inclination of the convex parts 4a and concave parts 4b. When the arithmetic mean height (Sa) is the same, a larger unfolded area ratio (Sdr) results in a larger number of convex parts 4a and concave parts 4b, while a smaller unfolded area ratio (Sdr) results in a smaller number of convex parts 4a and concave parts 4b. An unfolded area ratio (Sdr) of 0.05 to 0.2 results in a degree of inclination and quantity of the convex parts 4a and concave parts 4b of the uneven structure 4 that is suitable for low gloss and stain resistance. When the projected area when the uneven structure 4 is projected onto a flat surface is S1, and the difference between the actual surface area of ​​the uneven structure 4 and the projected area S1 is S2, the unfolded area ratio (Sdr), expressed as S2 / S1, is calculated as the average value measured at any ten points on the surface 3a of the active energy ray cured resin layer 3.

[0031] The surface area ratio (Sdr) is preferably 0.06 to 0.17. A surface area ratio (Sdr) of 0.06 to 0.17 allows the degree of inclination of the surface 3a of the active energy ray curable resin layer 3, as indicated by the surface area ratio (Sdr), to be more suitable for exhibiting both low gloss and stain resistance. As a result, the interior material 1 achieves a high level of both low gloss and stain resistance.

[0032] By having an uneven surface structure 4 that satisfies the surface roughness parameters (1) to (3) above, the uneven surface structure 4 on the surface 3a of the active energy ray curable resin layer 3 is suitable for exhibiting both low gloss and stain resistance, as indicated by the degree of protrusion (protrusion length) of the protrusions 4a, which is indicated by the degree of sharpness of the tips of the protrusions 4a, which is indicated by the mean arithmetic curvature (Spc) of the tips of the protrusions 4a, and the degree of inclination of the uneven surface structure 4, which is indicated by the developed area ratio (Sdr) expressed as S2 / S1, where S1 is the projected area when the uneven surface structure 4 is projected onto a flat surface, and S2 is the difference between the actual surface area of ​​the uneven surface structure 4 and the projected area S1. In other words, the performance exhibited by specifying the three surface roughness parameters described above, combined, results in a surface 3a of the active energy ray curable resin layer 3 having a fine uneven structure 4 that satisfies these surface roughness parameters, making it suitable for exhibiting both low gloss and stain resistance. As a result, the interior material 1 achieves a balance between low gloss and stain resistance.

[0033] Furthermore, by having an uneven surface structure 4 that satisfies the surface roughness parameters (1) to (3) above, chemical resistance is also achieved. This is thought to be because the uneven surface structure 4 provides a water-repellent effect due to the lotus effect, which reduces the amount of chemicals that come into contact with the surface 3a of the active energy ray cured resin layer 3. In addition, the increased density of the surface 3a of the active energy ray cured resin layer 3 is also thought to contribute to the improvement of chemical resistance.

[0034] The uneven structure 4 preferably further satisfies the surface roughness parameters (4) below. (4) The maximum height (Sz) is 5 to 50 μm.

[0035] The maximum height (Sz) is an indicator of the degree of local protrusion (protrusion length) of the convex portion 4a of the uneven structure 4. When the arithmetic mean height (Sa) is the same, the smaller the maximum height (Sz), the smaller the overall protrusion length of the convex portion 4a, and consequently, the smaller the overall depth of the concave portion 4b. On the other hand, when the arithmetic mean height (Sa) is the same, the larger the maximum height (Sz), the larger the locally larger the protrusion length of the convex portion 4a, and consequently, the larger the locally larger the depth of the concave portion 4b. In other words, even if the arithmetic mean height (Sa) is the same, the smaller the maximum height (Sz), the more homogenized the degree of protrusion of the uneven structure 4 is. A maximum height (Sz) of 5 to 50 μm is suitable for exhibiting both low gloss and stain resistance in terms of the degree of local protrusion (protrusion length) of the convex portion 4a indicated by the maximum height (Sz). As a result, in addition to the three surface roughness parameters mentioned above, the performance exhibited by specifying the maximum height (Sz) combines to make the surface 3a of the active energy ray curable resin layer 3 having the uneven structure 4 more suitable for exhibiting both low gloss and stain resistance. This allows the interior material 1 to achieve a high level of both low gloss and stain resistance. Furthermore, because the degree of protrusion of the uneven structure 4 is homogenized, chemical resistance is further improved. The maximum height (Sz) is calculated as the average value measured at any ten points on the surface 3a of the active energy ray curable resin layer 3.

[0036] The maximum height (Sz) is preferably 15 to 45 μm. By having a maximum height (Sz) of 15 to 45 μm, the uneven structure 4 on the surface 3a of the active energy ray curable resin layer 3 has its localized protrusion (protrusion length) of the convex portions 4a, which is indicated by the maximum height (Sz), suppressed, resulting in an overall homogenized uneven structure 4 that is even more suitable for exhibiting both low gloss and stain resistance. As a result, the interior material 1 achieves a higher level of balance between low gloss and stain resistance.

[0037] As described above, the surface 3a of the active energy ray curable resin layer 3 has an uneven structure 4 that satisfies the above surface roughness parameter, so that it can exhibit low gloss and antifouling properties even without containing powder such as silica. However, the active energy ray curable resin layer 3 may contain powder such as silica, as long as it does not interfere with the low gloss and antifouling properties achieved by the uneven structure 4 described above.

[0038] The active energy rays used in the present invention include, for example, light rays such as far ultraviolet rays, ultraviolet rays, near ultraviolet rays, infrared rays, and excimer laser light, as well as electromagnetic waves such as X-rays and gamma rays, and electron beams, proton beams, and neutron beams. The active energy ray curable resin used in the present invention refers to a resin that has been crosslinked and cured by irradiation with active energy rays, and can be obtained by irradiating an active energy ray curable resin composition with active energy rays using a known method. Among active energy ray curable resins, ultraviolet-curable resins or electron beam curable resins are preferably used, and ultraviolet-curable resins are more preferably used because they have excellent processability and are easy to handle.

[0039] The active energy ray curable resin contained in the active energy ray curable resin composition 30 is not particularly limited and can be set as appropriate. For example, the active energy ray curable resin composition 30 preferably contains a polyfunctional urethane acrylate and a polyfunctional acrylate monomer. By containing a polyfunctional urethane acrylate and a polyfunctional acrylate monomer in the active energy ray curable resin composition 30, a practical interior material 1 can be obtained that combines moderate elasticity derived from the polyfunctional urethane acrylate with moderate rigidity derived from the polyfunctional acrylate monomer.

[0040] Examples of polyfunctional urethane acrylates include difunctional urethane acrylate, trifunctional urethane acrylate, tetrafunctional urethane acrylate, pentafunctional urethane acrylate, and hexafunctional urethane acrylate, with difunctional urethane acrylate being preferred. By using difunctional urethane acrylate, a practical interior material 1 can be obtained that possesses a high level of appropriate elasticity derived from the polyfunctional urethane acrylate. Specific examples of polyfunctional urethane acrylates include, for example, phenylglycidyl ether (meth)acrylate hexamethylene diisocyanate urethane prepolymer, phenylglycidyl ether (meth)acrylate isophorone diisocyanate urethane prepolymer, phenylglycidyl ether (meth)acrylate tolylene diisocyanate urethane prepolymer, glycerin di(meth)acrylate tolylene diisocyanate urethane oligomer, pentaerythritol tri(meth)acrylate hexamethylene diisocyanate urethane oligomer, glycerin di(meth)acrylate isophorone diisocyanate urethane oligomer, pentaerythritol tri(meth)acrylate tolylene diisocyanate urethane oligomer, and pentaerythritol tri(meth)acrylate isophorone diisocyanate urethane pre-oligomer. These may be used individually or in combination of two or more types.

[0041] Examples of polyfunctional acrylate monomers include difunctional acrylate monomers, trifunctional acrylate monomers, tetrafunctional acrylate monomers, pentafunctional acrylate monomers, and hexafunctional acrylate monomers, with trifunctional acrylate monomers being preferred. By using a trifunctional acrylate monomer, a practical interior material 1 can be obtained that possesses a high level of appropriate rigidity derived from the trifunctional acrylate monomer. Furthermore, a surface roughness structure 4 that satisfies the above surface roughness parameters (1) to (3), and even (4), can be obtained more reliably. Examples of polyfunctional acrylate monomers include ethylene glycol diacrylate, diethylene glycol diacrylate, triethylene glycol diacrylate, tetraethylene glycol diacrylate, propylene glycol diacrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate, 1,3-propanediol diacrylate, 1,4-butanediol diacrylate, 1,5-pentanediol diacrylate, 1,6-hexanediol diacrylate, glycerol triacrylate, trimethylolethane triacrylate, trimethylolpropane triacrylate, pentaerythritol triacrylate, and dipentaerythritol triacrylate. These may be used individually or in combination of two or more.

[0042] The ratio (a:b) of the mass (a) of the polyfunctional urethane acrylate to the mass (b) of the polyfunctional acrylate monomer is, for example, 10 to 90:90 to 10, preferably 20 to 80:80 to 20, and more preferably 30 to 70:70 to 30. By having the ratio (a:b) of the mass (a) of the polyfunctional urethane acrylate to the mass (b) of the polyfunctional acrylate monomer within the above range, a superior interior material 1 can be obtained that has an appropriate viscosity, excellent coatability, and a good balance of elasticity and rigidity.

[0043] The total content of polyfunctional urethane acrylate and polyfunctional acrylate monomer in the active energy ray curable resin composition 30 is preferably 90% by mass or more, and more preferably 93% by mass or more. By having a total content of polyfunctional urethane acrylate and polyfunctional acrylate monomer in the active energy ray curable resin composition 30 of 90% by mass or more, the elasticity and rigidity described above due to the polyfunctional urethane acrylate and polyfunctional acrylate monomer can be more effectively exhibited.

[0044] The active energy ray curable resin composition 30 preferably contains a polymerization initiator. By containing a polymerization initiator in the active energy ray curable resin composition 30, after forming an uneven structure 4 on the surface 3a of the interior material 1, the active energy ray curable resin composition 30 can be reliably cured even to deep parts where active energy rays are difficult to reach. As a result, the strength of the interior material 1 is improved, and its practicality can be enhanced. As the polymerization initiator, a polymerization initiator that can polymerize without light irradiation can be used. Examples of such polymerization initiators include radical polymerization initiators such as benzoyl peroxide and azobisisobutyronitrile, in which polymerization is initiated by radicals generated by heating. In shallow parts where active energy rays can reach, it is of course possible to use photopolymerization initiators such as benzophenone, commercially available Omnirad 754, Omnirad 184, and Omnirad 127 (manufactured by IGM Resins BV). The content of the polymerization initiator in the active energy ray curable resin composition 30 is preferably 1 to 10% by mass, and more preferably 1 to 7% by mass.

[0045] The active energy ray-curable resin composition 30 may contain any additives, as long as they do not interfere with the low gloss and antifouling properties achieved by the above-described uneven structure 4. For example, the active energy ray-curable resin composition 30 may contain conventionally known organic solvents for adjusting viscosity by dilution, etc.

[0046] The thickness of the active energy ray curable resin layer 3 is preferably 5 to 50 μm, and more preferably 10 to 25 μm. By having a thickness of the active energy ray curable resin layer 3 equal to or greater than the lower limit, the active energy ray curable resin layer 3 can be made to have a uniform thickness. By having a thickness of the active energy ray curable resin layer 3 equal to or less than the upper limit, it becomes easier to form an uneven structure 4 that can exhibit low gloss and stain resistance.

[0047] The gloss (60°) of the surface 3a of the active energy ray cured resin layer 3 is preferably 5% or less. A gloss of 5% or less on the surface 3a of the active energy ray cured resin layer 3 results in the interior material 1 having superior low gloss, making dirt and scratches less noticeable. The gloss (60°) is measured by the measurement method described later.

[0048] <Characteristics of interior materials> The surface roughness parameters (Sa), (Spc), (Sdr), and (Sz), as well as the gloss (60°) of the surface 3a of the active energy ray curable resin layer 3 in the interior material 1, are as described above.

[0049] <Manufacturing method for interior materials> A manufacturing method for the interior material 1 includes a coating step of applying an active energy ray-curable resin composition 30 to a base material 2, a first irradiation step of irradiating the active energy ray-curable resin composition 30 with excimer laser light, and a second irradiation step of irradiating with ultraviolet light or an electron beam after the first irradiation step. Such a manufacturing method for the interior material 1 will be explained with reference to Figures 1(a) to (c).

[0050] First, as shown in Figure 1(a), an uncured active energy ray-curable resin composition 30 is applied to the surface 2a of the substrate 2 (coating step). The coating thickness of the active energy ray-curable resin composition 30 on the substrate 2 can be appropriately set so that the thickness of the active energy ray-curable resin layer 3 as a cured body is a desired value. For example, it can be 10 to 50 μm, preferably 15 to 25 μm, in accordance with the above-mentioned thickness of the active energy ray-curable resin layer 3. The coating method is not particularly limited, and various coating methods such as roll coaters, blade coaters, and curtain coaters are preferably used.

[0051] Next, as shown in Figure 1(b), excimer laser light (indicated as "EL" in Figure 1(b)) is irradiated onto the surface 30a of the coated active energy ray curable resin composition 30 from an excimer laser light irradiation device 51 (first irradiation step). Excimer laser light is light with a single wavelength peak that is emitted when an excited state molecule (excimer), which is composed of an excited state atom and a ground state atom, dissociates into two atoms. Examples of excimer laser light include excimer laser light with a wavelength of 126 nm emitted from an Ar2 excimer, excimer laser light with a wavelength of 146 nm emitted from a Kr2 excimer, excimer laser light with a wavelength of 157 nm emitted from an F2 excimer, excimer laser light with a wavelength of 172 nm emitted from a Xe2 excimer, and excimer laser light with a wavelength of 193 nm emitted from an ArF excimer. By using such excimer laser light, only the surface 30a of the active energy ray curable resin composition 30 can be partially cured. In this embodiment, an excimer laser light with a wavelength of 172 nm can be used. Due to its short wavelength, the excimer laser light cannot reach the interior of the active energy ray curable resin composition 30. Therefore, irradiation with the excimer laser light selectively cures the surface 30a of the active energy ray curable resin composition 30. As the surface 30a of the active energy ray curable resin composition 30 hardens, the interior does not harden and does not shrink. This difference in shrinkage force is mitigated by the formation of localized bulges, or irregularities, on the surface 30a. The irregularities that occur as a result of the mitigation of shrinkage force can be considered as wrinkles. In other words, the irregular structure can also be described as wrinkles. In this way, a surface-cured body (an active energy ray curable resin composition with a hardened surface) 31 is formed as an intermediate, in which the surface hardens and has an irregular structure 41, while the interior remains uncured. There are no particular limitations on the irradiation conditions for excimer laser light, but for example, a peak illuminance of 70-100 mW / cm² is used. 2 , integrated light intensity of 50-200 mJ / cm 2 It can be set to that.

[0052] Next, as shown in Figure 1(c), the surface 31a of the surface cured body 31 is irradiated with ultraviolet rays (indicated as "UV" in Figure 1(c)) from an ultraviolet irradiation device 52 (second irradiation step). These ultraviolet rays are ultraviolet rays having a wavelength larger than the wavelength of the excimer laser light. Examples of such ultraviolet rays include ultraviolet rays with a wavelength of 300 to 400 nm. Since the ultraviolet rays can reach the inside of the surface cured body 31, the entire body is thereby cured (that is, completely cured), and the active energy ray-curable resin layer 3 as a completely cured body having the uneven structure 4 on the surface is obtained. Note that the uneven structure 41 on the surface 31a of the surface cured body 31 becomes the uneven structure 4 on the surface 3a of the active energy ray-curable resin layer 3 in a substantially unchanged state. The uneven structure 4 has a plurality of convex portions 4a and a plurality of concave portions 4b. As for the ultraviolet irradiation conditions, it is preferable that both the peak illuminance and the integrated light amount are respectively larger than the peak illuminance and the integrated light amount of the excimer laser light. In this case, for example, the peak illuminance of ultraviolet rays can be set to 90 to 130 mW / cm 2 , and the integrated light amount to 400 to 800 mJ / cm 2 . Curing with ultraviolet rays is preferable from the perspective of improving production efficiency because it has excellent processability during manufacturing.

[0053] In this way, by applying the uncured active energy ray-curable resin composition 30 as a coating liquid onto the base material 2, irradiating the surface 30a of the applied active energy ray-curable resin composition 30 with excimer laser light, and then irradiating with ultraviolet rays, the interior material 1 in which the active energy ray-curable resin layer 3 is formed on the base material 2 can be obtained.

[0054] According to the manufacturing method of the interior material 1, by including the coating step, the first irradiation step, and the second irradiation step, an active energy ray curable resin layer 3 having a fine uneven structure 4 whose surface roughness parameters satisfy (1) to (3) above can be formed on the substrate 2. As a result, the performance exhibited by specifying the three surface roughness parameters combine to make the surface 3a of the active energy ray curable resin layer 3 suitable for exhibiting both low gloss and stain resistance. Therefore, according to the manufacturing method of the interior material 1, an interior material 1 that achieves both low gloss and stain resistance can be manufactured.

[0055] The surface roughness parameter of the uneven structure 4 on the surface 3a of the active energy ray curable resin layer 3 is preferably set to satisfy (1) to (3) above, and furthermore, to satisfy (4) above, by appropriately setting the type of active energy ray curable resin, the irradiation conditions of the excimer laser light, the irradiation conditions of ultraviolet light, etc. Alternatively, the laminate of the substrate 2 and the active energy ray curable resin composition 30 coated on the substrate 2 may be moved while irradiating with excimer laser light and ultraviolet light, in which case the cumulative light amount can be adjusted by appropriately setting the line speed.

[0056] Furthermore, although Figure 1(c) shows an example of irradiation with ultraviolet light, the method is not limited to this, and electron beam (EB) irradiation may be used instead of ultraviolet light. In this case, the active energy ray curable resin composition 30 does not require the addition of a photopolymerization initiator. [Examples]

[0057] Interior materials having the characteristic structure of the present invention (Examples 1-3) were fabricated and various measurements and evaluations were performed. For comparison, interior materials not having the characteristic structure of the present invention (Comparative Examples 1-3) were also fabricated and similar measurements and evaluations were performed.

[0058] [Examples 1-3] As ultraviolet-curable resins (hereinafter the same applies in the examples and comparative examples) used as active energy ray-curable resins, a bifunctional urethane acrylate and a trifunctional acrylate monomer were used. Active energy ray-curable resin compositions were obtained by mixing these bifunctional urethane acrylate and trifunctional acrylate monomer with polymerization initiators in the amounts shown in Table 1. The obtained active energy ray-curable resin compositions were applied to a rigid polyvinyl chloride tile as a substrate to a thickness of 25 μm, and interior materials of Examples 1 to 3 were obtained by irradiating with excimer laser light and then ultraviolet light under the irradiation conditions shown in Table 1, thereby laminating an active energy ray-curable resin layer on the substrate.

[0059] [Comparative Example 1] The interior material for Comparative Example 1 was obtained in the same manner as in Example 1, except that the irradiation conditions for the excimer laser light were set to the irradiation conditions shown in Table 1.

[0060] [Comparative Example 2] An active energy ray-curable resin composition was obtained in the same manner as in Example 1, except that a monofunctional acrylate monomer was used instead of a trifunctional acrylate monomer, and the blending amounts were as shown in Table 1. The obtained active energy ray-curable resin composition was applied to a rigid polyvinyl chloride tile as a substrate to a thickness of 25 μm, and an interior material of Comparative Example 2 was obtained by irradiating it with excimer laser light and then ultraviolet light under the irradiation conditions shown in Table 1, thereby laminating an active energy ray-curable resin layer on the substrate.

[0061] [Comparative Example 3] An active energy ray-curable resin composition was obtained in the same manner as in Example 1, except that matte silica powder was used in addition to the active energy ray-curable resin and polymerization initiator, and these were mixed in the amounts shown in Table 1. The obtained active energy ray-curable resin composition was applied to a rigid polyvinyl chloride tile as a substrate to a thickness of 25 μm, and by irradiating with ultraviolet light under the irradiation conditions shown in Table 1 without irradiating with excimer laser light, an active energy ray-curable resin layer having matte silica powder was laminated on the substrate to obtain the interior material of Comparative Example 3.

[0062] Figures 2-7 show photographs and three-dimensional images of the interior materials for Examples 1-3 and Comparative Examples 1-3. Figure 2(a) is a laser microscope image of the surface of the active energy ray cured resin layer, and Figure 2(b) is a three-dimensional image of the area captured by the laser microscope; both show the same area on the surface. That is, while Figure 2 shows a rectangular surface, Figure 2(b) shows that the long side is 277.243 μm and the short side is 207.32 μm, and these dimensions correspond to the long and short sides of the rectangle in Figure 2(a). Also, in Figure 2(b), the dimensions from the reference plane are 17.66 μm and -25.398 μm, and the sum of the absolute values ​​of these two represents the dimension from the peak of a peak to the bottom of a valley in the uneven structure. The numerical values ​​shown in Figures 3-7 are the same as those in Figure 2. Figures 2-7 are photographs and three-dimensional images of one point out of ten points each for Examples 1-3 and Comparative Examples 1-3.

[0063] The measurement and evaluation items in Examples 1-3 and Comparative Examples 1-3 are the arithmetic mean height (Sa), maximum height (Sz), average arithmetic curvature (Spc) of the tip of the protrusions as surface roughness parameters on the surface of the active energy ray cured resin layer, and the developed area ratio (Sdr) expressed as S2 / S1, where S1 is the projected area when the uneven structure is projected onto a flat surface, and S2 is the difference between the actual surface area of ​​the uneven structure and the projected area S1, as well as gloss, stain resistance, and chemical resistance. Each item is explained below.

[0064] [Surface roughness parameters] Using a white light interferometer-equipped laser microscope VK-X3000 (manufactured by Keyence Corporation), the surface of the active energy ray cured resin layer in the obtained interior material was photographed at 50x magnification and analyzed using the attached analysis tool. As a result, photographs of the surface of the active energy ray cured resin layer and 3D images of the photographed area were obtained. In addition, the arithmetic mean height (Sa), maximum height (Sz), mean arithmetic curvature of the tip of the protrusions (Spc) were used as surface roughness parameters, and the developed area ratio (Sdr), expressed as S2 / S1, was obtained when S1 is the projected area when the uneven structure is projected onto a flat surface, and S2 is the difference between the actual surface area of ​​the uneven structure and the projected area S1.

[0065] [Glossiness] Test specimens were obtained by cutting the interior material into 300mm x 300mm squares. After curing the test specimens for 24 hours under conditions of 23°C ± 2°C and 70% ± 15% humidity, the gloss (60°) of five arbitrary points on the surface of the active energy ray cured resin layer on the test specimen was measured using a gloss meter (model: IG-320, manufactured by Horiba, Ltd.), and the average value was calculated.

[0066] [Stain resistance (heel mark test)] Test specimens were obtained by cutting the acquired interior material into 22cm x 22cm squares. The surface of the base material (the side opposite to the active energy ray curing resin layer) of three test specimens was attached to the inner wall of a regular hexagonal prism-shaped hollow container. Six cubic rubber pieces, each measuring 5cm x 5cm x 5cm, were placed inside this hollow container. The container was then rotated clockwise for 15 minutes (rotation speed: 63 revolutions / minute), and then counterclockwise for 15 minutes (rotation speed: 63 revolutions / minute) to perform a heel mark test. After the rotation stopped, the test specimens were removed and visually observed under the following three conditions, and evaluated according to the following criteria. <Condition> Condition 1: Immediately after heel mark test (no wiping, immediately after the test) Condition 2: After wiping with a dry cloth (after dry wiping) Condition 3: After wiping with a damp cloth (after wiping with water) <Judgment criteria> A: No heel marks at all (good condition) B: Slight heel marks present (slightly defective) C: Many heel marks are present (defective)

[0067] [Chemical resistance] Test specimens were obtained by cutting the resulting interior material into 10cm x 10cm squares. A 1.5cm x 1.5cm square piece of absorbent cotton, approximately 5mm thick, was placed in the center of each test specimen, and 1.0mL of povidone-iodine (trade name: Isodine®) was soaked into the entire cotton. After ensuring sufficient contact between the test specimen and the absorbent cotton, a 9.0cm diameter watch glass was placed over the test specimen so as to cover the absorbent cotton, and the specimen was left undisturbed for 24 hours. After this, the absorbent cotton was removed, and the surface of the test specimen was washed with distilled water. After this treatment, the test specimens were visually inspected and evaluated according to the following criteria. <Judgment criteria> A: Uncolored (Good) B: Slightly discolored (slightly defective) C: Excessive coloring (defective)

[0068] Table 1 shows the composition of the interior materials for Examples 1-3 and Comparative Examples 1-3, as well as the measurement results and evaluation results. In Table 1, the unit of integrated light intensity is "mJ / cm". 2 The unit for peak illuminance is "mW / cm²". 2 "

[0069] [Table 1]

[0070] The interior materials of Examples 1-3 have surface roughness parameters of 0.5-6 μm for the surface of the activated energy ray curable resin layer, and an average arithmetic curvature (Spc) of 300-1300 μm. -1The materials had a spread area ratio (Sdr) of 0.05 to 0.2, and a maximum height (Sz) of 5 to 50 μm. These interior materials of Examples 1 to 3 had a gloss level (60°) of 5% or less, demonstrating excellent low gloss properties. Furthermore, they received an A rating for stain resistance under all three conditions: immediately after testing, after dry wiping, and after wet wiping, indicating excellent stain resistance. In addition, the interior materials of Examples 1 to 3 received an A rating for chemical resistance, demonstrating excellent chemical resistance.

[0071] In contrast, the interior material of Comparative Example 1 had surface roughness parameters such as mean arithmetic curvature (Spc) and unfolded area ratio (Sdr) that exceeded the specified numerical range. Figure 5 shows that although relatively clean wrinkles were formed on the surface of the active energy ray cured resin layer, the wrinkle density was high and the height difference was large. The interior material of Comparative Example 1 had a gloss level of 5% or less, indicating excellent low gloss, but its stain resistance was rated C immediately after the test, indicating poor stain resistance. Furthermore, the interior material of Comparative Example 1 received a B rating for chemical resistance, indicating poor chemical resistance.

[0072] The interior material of Comparative Example 2 had surface roughness parameters such as arithmetic mean height (Sa), mean arithmetic curvature (Spc), and developed area ratio (Sdr) that exceeded the specified numerical range. Figure 6 shows that uniform wrinkles were not formed on the surface of the active energy ray cured resin layer, but rather wrinkles were formed locally. The interior material of Comparative Example 2 had a gloss level of over 5%, indicating poor low gloss, and its stain resistance was evaluated as C immediately after the test and B after dry wiping, indicating poor stain resistance. Furthermore, the interior material of Comparative Example 2 received a B rating for chemical resistance, indicating poor chemical resistance.

[0073] The interior material of Comparative Example 3 had surface roughness parameters that were all below the specified numerical range. Specifically, the arithmetic mean height (Sa) and maximum height (Sz) were small, resulting in a small protrusion length of the convex parts; the mean arithmetic curvature (Spc) was small, resulting in a small sharpness of the convex parts; and the unfolded area ratio (Sdr) was close to 0, indicating a surface close to flat. Figure 7 shows that although very fine convex parts originating from matte silica were formed on the surface of the active energy ray cured resin layer, it was a substantially flat surface. The interior material of Comparative Example 3 had a gloss level of over 5%, indicating poor low gloss, and its stain resistance was rated C immediately after the test, indicating poor stain resistance. Furthermore, the interior material of Comparative Example 3 also had a chemical resistance rating of C, indicating poor chemical resistance. [Industrial applicability]

[0074] This invention is a technology that can be widely used as interior materials in the construction industry, renovation industry, etc., and is particularly useful in situations where interior materials, especially flooring materials, are installed in various buildings such as general houses, apartment buildings, condominiums, commercial malls, office buildings, factories, shops, train stations, schools, hospitals, and public facilities. [Explanation of symbols]

[0075] 1. Interior materials 2 Base material 3. Active energy ray curable resin layer 3a surface 30 Active energy ray curable resin composition 4 Uneven structure

Claims

1. An interior material comprising a base material and an active energy ray curable resin layer laminated on the base material, the active energy ray curable resin layer being made of a cured body of an active energy ray curable resin composition, The active energy ray curable resin composition comprises a polyfunctional urethane acrylate and a polyfunctional acrylate monomer. The surface of the activated energy ray curable resin layer has an uneven structure as wrinkles that satisfies the surface roughness parameters (1) and (3) below. An interior material having a gloss level (60°) of 5% or less on the surface of the activated energy ray cured resin layer. (1) The arithmetic mean height (Sa) is 0.5 to 6 μm. (3) When the projection area of ​​the uneven structure is projected onto a flat surface is S1, and the difference between the actual surface area of ​​the uneven structure and the projection area S1 is S2, the unfolded area ratio (Sdr) expressed as S2 / S1 is 0.05 to 0.

2.

2. The interior material according to claim 1, wherein the aforementioned uneven structure further satisfies the surface roughness parameter (4) below. (4) The maximum height (Sz) is 5 to 50 μm.

3. A method for manufacturing interior materials according to Claim 1 or 2, A coating step of applying the active energy ray curable resin composition to the substrate, A first irradiation step involves irradiating the active energy ray curable resin composition with excimer laser light, A second irradiation step is performed after the first irradiation step, in which ultraviolet light or an electron beam is irradiated. A method for manufacturing interior materials containing [materials].

Citation Information

Patent Citations

  • Method of manufacturing building material

    JP2018164901A

  • Decorative sheet and method for producing the same

    JP2021024102A

  • Decorative sheet

    JP2021165033A

  • Matte article and method for manufacturing same

    JP2022008024A

  • Matte article

    JP2022048109A